Discourses on Twitter contribute to the concept of resilience in the LGBT community in Malaysia / Muhammad Naim Muhammad Ali and Noor Mayudia Mothar - Muhammad Ali, Muhammad Naim; Mothar, Noor Mayudia (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
The purpose of this study is to understand the issues discussed revolving the LGBT community in Malaysia based on Twitter content that contribute to concept of resilience. The study used content analysis approach to study the Twitter postings that discuss LGBT issues, particularly to between March 8, 2019, to March 10, 2019, because during the period, Women’s March was held in Kuala Lumpur and participated by LGBT individuals to promote inclusivity towards them which considered very controversial Malaysia. Based on the literature review, the researcher able to construct a framework for the study and has selected the resilience theory as a guide to answering the objectives. Resilience theory discusses the impact of facing challenging events on individuals, family, or community and how they adapt to the traumatic experience. The concept of resilience is defined as a coping mechanism to stressors in positive manners, which in this study, the emerged themes that categorized into smaller sub-themes. The researcher used qualitative content analysis approach by conducting latent or manifest analysis to transcribe the context of the Twitter content in order to categorize the issues discussed on Twitter. The concept of resilience were found in many of the Twitter postings which explained in the findings.